Guillain–Barré syndrome (GBS) following tetanus vaccination - Cristoss Gregory; Atanu Basu; Akhil Tomy; Jacob Sebastian; Jose James; Tanushree Dewan (Clinical Medicine)
Introduction: Guillain–Barré syndrome (GBS) is the most common cause of acute flaccid paralysis. All administered age groups can be affected, although it is more common in older patients.1 Respiratory failure occurs in about one-third of GBS patients, correlating with severe, rapidly progressive disease. GBS is frequently preceded by infection, with about two-thirds of patients experiencing preceding gastrointestinal or respiratory infections.2 Pathogens associated with GBS include Campylobacter jejuni, Epstein–Barr virus and influenza. Reports also link GBS to vaccinations, such as those for meningococcal disease, poliovirus, influenza, rabies and Coronavirus 2019 (COVID-19).3 Here, we describe a rare case of a man in his 60s who developed bilateral lower limb weakness and was diagnosed with GBS following a tetanus vaccination after a dog bite. The temporal pattern of GBS onset post-vaccination resembled that seen following infection. Method and materials: A man in his late 60s presented with a 2-week history of bilateral lower limb weakness, breathing difficulty, and upper limb numbness and tingling. He had received a tetanus vaccination 3 weeks prior after a dog bite. His initial symptoms included difficulty walking upstairs, progressively worsening weakness and hypertension, but no recent illness, fever or diarrhea. On admission, examination revealed significant proximal lower limb weakness, normal sensations and muscle tone, and lower limb areflexia. Lumbar puncture showed elevated protein and IgG levels. Neurological evaluation and intravenous immunoglobulin therapy were initiated. Tests for various antibodies and infections were negative. Daily functional vital capacity (FVC) monitoring showed initial decline, then improvement. Electromyography (EMG) indicated absent median and ulnar sensory responses, normal sural nerve, prolonged distal motor latencies and dispersed compound muscle action potentials (CMAPs). Computed tomography (CT) scans ruled out malignancies, and symptoms improved with physiotherapy. Discussion: This case involved a man with progressive muscle weakness, areflexia and albumin-cytologic dissociation. Neurophysiological examinations indicated axonal or demyelinating damage, confirming GBS. The absence of infections and negative serological tests suggested the tetanus vaccination as the trigger. GBS is usually preceded by infection or any immune stimulation that induces an autoimmune response targeting peripheral nerves.7 Therefore, the mechanism of GBS after vaccination can be explained with this theory.4 While a significant association between GBS and influenza vaccines is documented, evidence regarding DTP vaccines is limited. Sporadic GBS cases following DTaP or tetanus toxoid-containing vaccines have been reported since 1978.4 A study in the American Journal of Public Health (1997) indicated that any association is unlikely to be significant at the public health level.5 The Advisory Committee on Immunization Practices (USA) considers GBS development within 6 weeks post-tetanus vaccination as a precaution for subsequent vaccinations.6 Conclusion: This case confirmed GBS through clinical presentation and diagnostic tests, identifying tetanus vaccination as the only risk factor, suggesting a causal relationship. It underscores the importance of recognising GBS as a potential adverse event following tetanus vaccination and the need for vigilance in monitoring and reporting such cases.